ESTRATÉGIAS DISCURSIVAS DE INFORMALIDADE E ENVOLVIMENTO EM GÊNEROS ESCRITOS - Heberle, Viviane M. (Intercâmbio, 2010)
Abstract: Based on principles of discourse analysis and also of critical discourse analysis, I present considerations on discursive strategies of informality and/or proximity in several types of written texts. I analyze the use of a) discourse markers such as adverbs and interjections; b) interrogative clauses; c) observations in parentheses; and d) direct speech. These strategies show writers’ concern to establish involvement and interactional alignment with the audience.